Structural and Phase Transformations in Water-Vapour-Plasma-Treated Hydrophilic TiO2 Films - L. Pranevicius; M. Urbonavicius; S. Tuckute; K. Gedvilas; T. Rajackas; L. L. Pranevicius; D. Milcius (Advances in Materials Science and Engineering)
We have investigated structural and phase transformations in water-vapor-plasma-treated 200–300 nm thick Ti films, maintained at room temperature, by injecting water vapor into radio frequency (RF) plasma at different processing powers. Scanning electron microscopy (SEM) combined with optical microscopy and surface nanotopography analysis were used to view tracks of adsorbed water layers and to detect bulges or blisters appeared on the surface of treated samples. Rough surfaces with different size of holes (5–20 μm) through the entire film thickness have been observed. X-ray diffraction results show that the oxidation rate of Ti film drastically increases in the presence of an adsorbed water on the hydrophilic layer. It is assumed that the defining factor which controls oxidation kinetics is the hydroxyl radicals formation.